The Effectiveness of Crossword Puzzle in Teaching Vocabulary of Fourth Grade Elementary Students - Zainata Illiyin (ELITE JOURNAL, 2023)
ABSTRACTEnglish is an international language in the world and it is used as foreign language in Indonesia. English is not our native language, therefore it is very difficult for Indonesian students to learn it. Besides, Bahasa Indonesia and English are not related languages. There are many elements found in them like grammatical and different pronunciation. Same with Bahasa Indonesia, English also has four basic aspects, there are speaking, listening, reading and writing. In this study, the writer want to research the effectiveness of crossword puzzle in teaching vocabulary to improve English skills aboveThe aim of this study was to find out whether the use of crossword puzzle related to things in the classroom, parts of human body, and fruits could increase elementary students in learning vocabulary. The approach of this study was quantitative. Vocabulary tests were used as the instruments of eliciting the data. The subjects of this study were the fourth grade students of MI Raudlatul Ulum Rejoyoso. The results showed that there was an increase between the pre-test (46.67) and the post-test (61.24). The difference between the pre-test and the post-test was statistically significant (0.00<0.05). This indicates that crossword puzzle increased students’ vocabulary achievement. Vocabulary regarding parts of human body got the highest increase (3.7) compared to the other two topics, things in the classroom (3.1) and fruits (2.5) respectively. This suggests that realia can be used as alternative media in teaching vocabulary. Keywords: Crossword puzzle, vocabulary, quantitative research.